Performance of structural glass facades under extreme loads – Design methods, existing research, current issues and trends. (28th February 2018) - Bedon, Chiara; Zhang, Xihong; Santos, Filipe; Honfi, Dániel; Kozłowski, Marcin; Arrigoni, Michel; Figuli, Lucia; Lange, David
Graphical abstract: Highlights: Glass in windows and facades is largely used, for many practical reasons. Material intrinsic features make glass facades one of the most vulnerable component of buildings. Fail-safe design requirements are mandatory, especially under extreme loads. Design methods for some key extreme design actions are analysed. Abstract: Glass has been overwhelmingly used for windows and facades in modern constructions, for many practical reasons, including thermal, energy, light and aesthetics. Nevertheless, due to the relatively low tensile strength and mostly brittle behaviour of glass, compared to other traditional materials, as well as to a multitude of interacting structural and non-structural components, windows/facades are one of the most fragile and vulnerable components of buildings, being representative of the physical line of separation between interior and exterior spaces. As such, multidisciplinary approaches, as well as specific fail-safe design criteria and analysis methods are required, especially under extreme loading conditions, so that casualties and injuries in the event of failure could be avoided and appropriate safety levels could be guaranteed. In this context, this paper presents a review of the state of art on analysis and design methods in use for glass facades, with careful consideration for extreme loading configurations, including natural events, such as seismic events, extreme wind or other climatic exposures, and man-made threats, i.e. blast loads and fire. Major results of available experimental outcomes, current issues and trends are also reported, summarising still open challenges.